Modelagem numérica aplicada ao estudo da origem e evolução morfológica dos esporões da Lagoa de Araruama - RJ - Alves, Albano Ribeiro (2006)
The Lagoa de Araruama lagoon cuspate spits have been studied here throughout numerical modeling and image processing. The two years long hindcasting of wave parameters was performed through SWAN model. Snell s Law and energy conservation have achieved the propagation of these wave parameters into the breaker zone near to the beach. By this way, the potential sediment transported longshore rate was computed in seventeen points around the central cuspate spit in its south edge. The results analyzed through sediment continuity equation have showed that the sediment flux have been from the tip to base in this feature. This unexpected behavior might be a sign of an erosive stage on its tip and a progradation on its base. The overlay of both images 1954 aerial photography and 2006 field data of the shoreline position have agreed with the modeled predictions. So, if these environmental sets last longer the shoreline will be reoriented counterclockwise until will reach again a stage that would promote the lagoon segmentation as was predict in classical literature.